A benzothiazole-based fluorescent probe for efficient detection and discrimination of Zn2+ and Cd2+, using cysteine as an auxiliary reagent - Li, Jia; Chen, Yahui; Chen, Tiantian; Qiang, Jian; Zhang, Zhijie; Wei, Tingwen; Zhang, Wei; Wang, Fang; Chen, Xiaoqiang (Sensors and actuators. B, Chemical, 2018)
•A new benzothiazole-based sensing system was provided for detection of Zn2+ and Cd2+ by employing cysteine as an auxiliary regent.•A new verification method of aggregation by fluorescence polarized emission was developed.•The sensing system can detect Zn2+ and Cd2+ with the level of nanomole and micromole detection limit, respectively. This paper describes the design and synthesis of a benzothiazole-based fluorescent probe (H1) for zinc and cadmium ion detection and discrimination, using cysteine as an auxiliary reagent. Among the various metal ions tested, zinc and cadmium ions induced blue-shifted emissions of probe H1 from 573 nm to 520 nm and 540 nm, respectively. The addition of cysteine caused the emission of H1-Cd2+ to red-shift back to 573 nm. In contrast, the emission of H1-Zn2+ with the addition of cysteine only decreased without any red-shift of wavelength. Furthermore, confocal laser scanning micrographs of HeLa cells demonstrated satisfactory cell permeability of H1 and selectivity toward zinc and cadmium ions in living cells. Test strip experiments suggest that probe H1 can recognise zinc and cadmium ions together by a remarkable fluorescence change, thus providing a convenient method for tracking zinc and cadmium ions in biological systems.